Pengaruh Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Karya Solusi Prima Sejahtera Di Jakarta Selatan - Sherly Apriani; Fahmi Susanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study is to determine the partial and simultan effects of Work Environment and Organizational Commitment on Employee Performance at PT Karya Solusi Prima Sejahtera. The method used in this research is quantitative with an associative approach, which aims to identify the relationship between two or more variables. The sampling technique used is saturated sampling, and data were collected through questionnaires, resulting in 81 respondents. Data analysis was carried out using SPSS version 26. The analytical techniques employed include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the study show that the Work Environment has a significant effect on Employee Performance, with a coefficient of determination of 48.1%, and the hypothesis test results show t-count > t-table (8,557 > 1.665). Organizational Commitment also has a significant effect on Employee Performance, with a coefficient of determination of 34.4%, and the hypothesis test results show t-count > t-table (6,440 > 1.665). Furthermore, the Work Environment and Organizational Commitment simultaneously have a significant effect on Employee Performance, with the regression equation Ŷ = 7.747 + 0.552X1 + 0.251X2, and a correlation value of 0.587. The coefficient of determination is 0.523 (52.3%), while the remaining 47.7% is explained by other factors. The hypothesis testing shows that F-count > F-table (42.715 > 3.115), indicating that the model is statistically significant